2013
DOI: 10.1080/02640414.2013.777763
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lower limb internal kinetics and electromyography in elite race walking

Abstract: The aim of this study was to analyse lower limb joint moments, powers and electromyography patterns in elite race walking. Twenty international male and female race walkers performed at their competitive pace in a laboratory setting. The collection of ground reaction forces (1000 Hz) was synchronised with two-dimensional high-speed videography (100 Hz) and electromyography of seven lower limb muscles (1000 Hz). As well as measuring key performance variables such as speed and stride length, normalised joint mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 18 publications
5
47
0
Order By: Relevance
“…During ankle joint dorsiflexion, in the early phase of the stance period, the body decelerated while the plantar flexor torque, from 60 to 100% of stance period, is fundamental to gain the forward propulsion (Cairns et al, 1986;White & Winter, 1985), and it is strongly correlated to the speed (Figure 3). However recently Hanley and Bissas (2013) proved that ankle torque is not the only power generator, but hip extensors and ankle plantarflexors moments are also fundamental to accelerate the body centre of mass through an energy transfer from the hip to the ankle via the straightened knee. The absorbing power obtained during the knee flexion before toe off is crucial to provide more time to the swinging leg in order to land ahead and avoid flight phase.…”
Section: Joint Power Energy Flow and Efficiencymentioning
confidence: 99%
See 4 more Smart Citations
“…During ankle joint dorsiflexion, in the early phase of the stance period, the body decelerated while the plantar flexor torque, from 60 to 100% of stance period, is fundamental to gain the forward propulsion (Cairns et al, 1986;White & Winter, 1985), and it is strongly correlated to the speed (Figure 3). However recently Hanley and Bissas (2013) proved that ankle torque is not the only power generator, but hip extensors and ankle plantarflexors moments are also fundamental to accelerate the body centre of mass through an energy transfer from the hip to the ankle via the straightened knee. The absorbing power obtained during the knee flexion before toe off is crucial to provide more time to the swinging leg in order to land ahead and avoid flight phase.…”
Section: Joint Power Energy Flow and Efficiencymentioning
confidence: 99%
“…It can be addressed to a varying reference selection for joint angle measurement: Hanley et al (2011a) estimated pelvic angle using hip joint coordinates, whereas Murray et al (1936) and Cairns et al (1986) calculated the whole angular rotation of the same marker. Differently Murray et al (1983), White and Winter (1985) and Hanley and Bissas (2013) showed hip, knee and ankle joint angular time course during a stride, which may be an important functional parameter for a more complete picture of the locomotion pattern and to provide coaches and athletes with a further technical feedback suitable in training.…”
Section: Kinematicsmentioning
confidence: 99%
See 3 more Smart Citations